Supervision and Guidance Implementation on Notaries by Regional Supervisory Council & Legal Consequences - Annisa Mahardani Tasruddin; Ahmad Khisni; Munsharif Abdul Chalim (Sultan Agung Notary Law Review, 2021)
The purpose of this study is to determine the implementation of Notary supervision carried out by MPD, the performance of Notaries based on the results of Notary supervision by MPD, and to find out the obstacles faced by MPD in carrying out Notary supervision in their area. The approach method in this research is normative juridical. The research specification is descriptive analytical. The data sources used in this study consist of primary data and secondary data which can be distinguished in primary legal materials, secondary legal materials, and tertiary legal materials. Collecting data in this study using the method of literature study and interviews. The data analysis technique used is the processed data which will be presented in the form of qualitative data analysis. Based on this research, it can be concluded that the Notary has the legal authority to make an authentic deed. In order to improve the quality and quantity of Notaries, a new regulation that applies to Notaries is issued, namely Act No. 30 of 2004 concerning Notary Positions (UUJN). Along with the accountability of the Notary to the community in carrying out his duties, then it must be guaranteed by the existence of a supervision and guidance. Notary supervision is carried out by involving several elements, namely experts from academics, government elements, and notary elements.